(untitled) (Texas Journal of Philology, Culture and History, 2026)
This article examines the lexical and semantic means of expressing moral support in the English and Russian languages. The study analyzes linguistic units, communicative expressions, and stylistic devices used to convey emotional encouragement, empathy, consolation, and psychological assistance in interpersonal communication. Special attention is paid to the comparative analysis of culturally specific and universal features of moral support in both languages. The research also explores the pragmatic and sociolinguistic aspects of supportive speech acts and their role in effective communication